2017
DOI: 10.1371/journal.ppat.1006664
|View full text |Cite
|
Sign up to set email alerts
|

EBF1 binds to EBNA2 and promotes the assembly of EBNA2 chromatin complexes in B cells

Abstract: Epstein-Barr virus (EBV) infection converts resting human B cells into permanently proliferating lymphoblastoid cell lines (LCLs). The Epstein-Barr virus nuclear antigen 2 (EBNA2) plays a key role in this process. It preferentially binds to B cell enhancers and establishes a specific viral and cellular gene expression program in LCLs. The cellular DNA binding factor CBF1/CSL serves as a sequence specific chromatin anchor for EBNA2. The ubiquitous expression of this highly conserved protein raises the question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 80 publications
5
34
0
Order By: Relevance
“…In addition to the presence of an EBNA2-bound super-enhancer upstream of the neighboring DUSP22 gene ( 27 ), we found that EBNA2 can also upregulate IRF4 transcription through an RBPJ-dependent enhancer located in an intergenic region 13 kb upstream from IRF4 . This is consistent with recent reports of IRF4 as an RBPJ-dependent EBNA2 target gene ( 40 ). At IRF4 and DUSP22 , EBNA2 therefore likely targets multiple enhancers and super-enhancers.…”
Section: Discussionsupporting
confidence: 94%
“…In addition to the presence of an EBNA2-bound super-enhancer upstream of the neighboring DUSP22 gene ( 27 ), we found that EBNA2 can also upregulate IRF4 transcription through an RBPJ-dependent enhancer located in an intergenic region 13 kb upstream from IRF4 . This is consistent with recent reports of IRF4 as an RBPJ-dependent EBNA2 target gene ( 40 ). At IRF4 and DUSP22 , EBNA2 therefore likely targets multiple enhancers and super-enhancers.…”
Section: Discussionsupporting
confidence: 94%
“…We found that miR-34a downregulation by EBNA2 likely involves recruitment of EBF1 at the miR-34a promoter. Glaser et al have recently shown that EBF1 interacts with the N-terminal portion of EBNA2 in a B-cell specific manner and this interaction promotes EBNA2 access to chromatin, without involving RBPJk, a known EBNA2-DNA anchor [19]. Our analysis of EBNA2 ChIP-Seq datasets from GEO database (accession number: GSM2039170) revealed that EBNA2 peaks at the miR-34a promoter.…”
Section: Discussionmentioning
confidence: 78%
“…It does not bind directly to DNA but activates transcription of many target genes by binding to the transcription factor, RBP-Jk [17]. EBNA2 colocalizes with another B-cell-specific DNA binding transcription factor, EBF1 [16], which is essential for the commitment and maintenance of B-cell transcription program [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…EBNA3A ChIP-seq has demonstrated that EBNA3A binding sites are less enriched for EBF1 than EBNA3C or EBNA3B binding sites ( 13 ). The cellular factor EBF1 has been shown to interact with the EBV transcription factor EBNA2 and recruits the viral protein to a specific genomic location ( 41 , 42 ). However, EBNA2 does not seem to be involved in the STK39 mRNA regulation ( 43 , 44 ), and no EBNA2 binding site has been found at STK39 in EBNA2 ChIP-seq studies ( 33 ).…”
Section: Discussionmentioning
confidence: 99%